The shape of spectatorship : art, science, and early cinema in Germany. - Curtis, Scott (Film and culture., 2015)
In this exceptionally wide-ranging study, Scott Curtis draws our eye to the role of scientific, medical, educational, and aesthetic observation in shaping modern conceptions of spectatorship. Focusing on the nontheatrical use of motion picture technology in Germany between the 1890s and World War I, he follows specialists across disciplines as they debated and appropriated film for their own ends, negotiating the fascinating, at times fraught relationship between technology, discipline, and expert vision.